The North Caucasus Russias volatile frontier - Kuchins, Andrew 1959-; Malarkey, Matthew; Markedonov, Sergej M. 1972- (Center for Strategic and International Studies, 2011)
To best face and contend with the known and emerging threats in the North Caucasus requires an informed picture and understanding of what is going on in the region. This report sheds light on some of the most important trends that are taking place and in turn raise awareness of the most salient issues affecting the region today. It will then promote practical approaches that can be taken both in Moscow and the West to better and more effectively address and alleviate the deteriorating situation in the North Caucasus